Jemput²: the development of mobile application for locating nearby travel buddy to explore local food / Muhammad Syabil Iqbal Mohamed Rashdan - Mohamed Rashdan, Muhammad Syabil Iqbal (2019)
Malaysia is listed as one of the hotspots for travelling destination as it is famously known for its extremely diversified cultures, ethnicity, languages, religions and most importantly food. Unfortunately, the Malaysian local food is poorly being promoted and highlighted in the international market. There are many mobile applications that are related to travel partner or travel buddy searching in the market but non-of the mobile application is focused on promoting the Malaysian local food. Thus, the objectives of this project are to identify the user requirements of Jemput² mobile application for locating nearby local food restaurants and to explore the local food with a travel buddy, to design and to develop the Jemput² mobile application. The scope of this project is for user to locate nearby local food restaurants and find a travel buddy nearby to enjoy the local food together. This project uses the Design Thinking methodology to develop the Jemput² mobile application. The Design Thinking methodology is divided into 5 phase which are Empathize, Define, Ideate, Prototype, and Testing. The findings of this project is the travelers have a few problems in exploring local food. Firstly, travelers often define on web recommendation to find places that they are going to visit and to look for places to eat which might be biased. Besides, there are many applications that are related to travel partner searching in the market but non- of the mobile application is focused on promoting Malaysian local food that is already widely known for their own uniqueness, variety and culture-related. This point is supported by interviews that have been conducted with 3 travelers that have more than 5 years of travelling experiences. Based on the interviews, the travelers also claimed that it is hard to know whether the origin of the food that are eating in Malaysia is indeed a local Malaysian dish. Thus the result of this project is a mobile application that will locate nearby Malaysian local food restaurants and stalls as well as nearby travel buddies to enjoy the Malaysian local food together to help improve the gastronomic experience and to give more genuine tips about the local food.